Где ночуют призраки: [повесть] / Анна Дубчак - Дубчак Анна Васильевна (Любимые книги девочек, 2003)
Экземпляры: ф.22 (2003) / Инвентарный номер: 46582 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: Д 79 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44